Природне відновлення дубових насаджень Лівобережного Лісостепу після проведення в них лісовідновних рубок - Tkach, V. P.; Rumіantsev, M. Н.; Luk’yanets, V. A. (Ukrainian Research Institute of Forestry and Forest Melioration named after G. M. Vysotsky (URIFFM), 2023)
Introduction Natural seed regeneration of oak stands in the Left-Bank Forest-Steppe of Ukraine has recently received considerable attention. This is due to the negative trend of reducing the area of natural oak forests. Therefore, one of the important aspects of forest management in oak forests during their reproduction is the effective use of natural regeneration of oak and other valuable species, as well as the activities to promote it. The study aims to identify the features of the natural regeneration of English oak (Quercus robur L.) and other valuable species on clear-cuts after the strip-gradual regeneration felling. Materials and Methods The study was conducted in the forests of Kharkiv Forest Research Station in fresh fertile site conditions in 105–110-year-old oak stands of vegetative origin with a relative density of stocking of 0.72–0.84 and 80–100% of Q. robur in the composition. Strip-gradual regeneration felling (continuous cutting of trees in strips 25 m wide) was carried out in the stands in combination with natural regeneration-promoting activities. All clear-cuts were left for further natural regeneration. The success of natural regeneration was evaluated according to the scale developed in URIFFM. The numbers of plants in young stands were assessed on circular accounting sites of 10 m2 and the main mensuration characteristics were determined. Results The fructification intensity significantly affects the number of developed acorns and, accordingly, the success of the natural regeneration of oak forests. In the 13-year-old stand developed after strip-gradual regeneration felling in the year of good acorn harvest, the number of English oak trees was 12.6 thousand per ha (75% of the total). In the 8-year-old stand developed after strip-gradual regeneration felling in the year of a very good acorn harvest, the number of English oak trees was the largest – 19.3 thousand stems per ha (85% of the total). In the 4-year-old stand developed after strip-gradual regeneration felling in the year of medium acorn harvest, the number of English oak trees was 17.2 thousand per ha (60% of the total number). In the 6- and 7-year-old stands developed after strip-gradual regeneration felling after a year with a poor acorn harvest, the number of English oak trees was generally sufficient and amounted to 7.0–8.2 thousand per ha (58–84% of the total number). In the 2-year-old young stands developed after strip-gradual regeneration felling after a year with a very poor acorn harvest, even in combination with regeneration-promoting activities, the number of English oak trees was only 0.7 thousand per ha (8% of the total number). The success of natural regeneration according to the scale developed in URIFFM in the clear-cuts after the strip-gradual regeneration felling in weakened coppice oak stands after years of medium, good, and very good acorn harvest was assessed as “good”. The natural regeneration success was assessed as “satisfactory” in clear-cuts with additional acorn sowing in places without oak saplings. In the clear-cut area after a year of very low and low oak harvests without additional acorn sowing the natural regeneration success was assessed as “insufficient”. Measures to ensure the successful seed natural regeneration of oak forests are proposed. Conclusions The success of the natural regeneration of oak forests largely depends on the intensity and periodicity of oak fructification, as well as on the previous implementation of certain forestry activities. These points should be taken into account to promote the natural seed regeneration of oak stands in the Left-Bank Forest-Steppe of Ukraine. 1 Fig., 3 Tables, 30 Refs.